PWE-023 Vitamin D Enhances The Ability of Anti-TNF Therapy to Suppress Dendritic Cell Activity in Crohn's Disease. (17th August 2016) - Hendy, PA; Reddi, D; Barnardo, D; Durant, L; Noble, A; Bhat, P; English, N; Knight, SC; Hart, AL
Abstract : Introduction: Dendritic cells (DC) can determine whether the mucosal immune system mounts an inflammatory or regulatory response to antigen and may contribute to the pathogenesis of Crohn's disease. Vitamin D down-regulates DC inflammatory responses and could prove beneficial as a treatment adjunct in Crohn's. This study assessed the effect of high dose parenteral vitamin D treatment on circulating DC phenotype and function in patients with active luminal Crohn's receiving anti-TNFα therapy. Methods: Peripheral blood mononuclear cells were isolated from 13 patients with active luminal Crohn's and suboptimal vitamin D levels prior to and 6 weeks after starting anti-TNFα (infliximab) therapy. Patients with low vitamin D (<50nmol/L) were also given a single high dose of parenteral vitamin D (300, 000 international units 1, 25(OH)2 vitamin D3). Flow cytometry was used to identify total DC, (HLA-DR + cells negative for markers of other cell lineages (CD3, CD14, CD16, CD19 & CD34)). DC were further subtyped as myeloid (mDC, CD11c + CD123 − ). Expression of phenotypic markers (including maturation and homing markers and pattern recognition receptors) and on-going DC cytokine production during 4 hours' culture were assessed. Results: Production of TNFα by myeloid DC was significantly reduced (p = 0.016 Fig C) in those patients who received vitamin D alongside anti-TNFα therapy; without vitamin D treatment, TNFα production by myeloid DC did not decrease significantly after anti-TNFα therapy (p = 0.96 Fig B). There was a significant negative correlation between change in vitamin D level and change in TNFα production by myeloid DC (p = 0.025, correlation coefficient =0.68 Fig D). An increase of serum 25(OH)vitamin D greater than 20 nmol/m was associated with a decrease in myeloid DC TNFα production. Anti-TNFα therapy alone induced a significant upregulation of the skin homing marker cutaneous lymphocyte antigen (CLA) on myeloid DC (p = 0.0055), an effect which was not seen in patients receiving adjunctive vitamin D. Conclusion: High doses of parenteral vitamin D in patients with Crohn's promotes anti-TNFα down-regulation of circulating myeloid DC production of TNFα which may influence the subsequent interaction of DC and T cells. TNFα promotes a TH-1/ TH-17 response characteristic of Crohn's inflammation; thus the ability of vitamin D to further block TNFα production may promote a more regulatory T cell response and improve outcomes when used as an adjunct to anti-TNFα therapy. The down-regulation of skin homing marker CLA by vitamin D may be clinically useful in those patients suffering cutaneous sequelae of anti-TNFα therapy. Disclosure of Interest: None Declared